Analysis of a Holistic-Comprehensive Health Service Approach in Menopause: A Systematic Literature Review - Mariska, Ika (Archives of The Medicine and Case Reports, 2024)
Menopause is a natural phase experienced by women. This phase is characterized by the cessation of ovulation and menstruation, as well as a decrease in the production of the hormones estrogen and progesterone. Menopause can cause a variety of physical and psychological symptoms, such as hot flashes, night sweats, mood swings, and sleep disturbances. A holistic comprehensive health service approach to menopause is an approach that views women as a complete unit, both physically, psychologically, socially, and spiritually. This approach aims to provide optimal health services by paying attention to various aspects that can affect the health of menopausal women. This study aims to analyze a holistic-comprehensive health service approach to menopause. This research was carried out using systematic literature review method. Research data was obtained from 15 journal articles published in the period 2010-2022. The research results show that a holistic-comprehensive health service approach to menopause includes three main aspects, namely: Physical aspects, including examination and treatment of physical symptoms of menopause, such as hot flashes, night sweats, mood swings and sleep disorders; Psychological aspects, including counseling and psychosocial therapy to help menopausal women deal with physical and emotional changes; Social aspects, including family and community support to help menopausal women adapt to changes in their role and status. A holistic-comprehensive health care approach to menopause can provide significant benefits for menopausal women, such as: Improving the quality of life of menopausal women; Reduces the risk of menopausal complications; Increasing menopausal women's satisfaction with health services.